Isolation of a chicken gene that confers susceptibility to infection by subgroup A avian leukosis and sarcoma viruses. - Young, J A (1993)
We used a genetic strategy to isolate the chicken gene believed to encode the receptor for subgroup A avian leukosis and sarcoma viruses (ALSV-A). Chicken genomic DNA was transfected into monkey COS-7 cells, and two independent primary transfectants susceptible to ALSV-A infection were identified by using ALSV-A vectors containing a hygromycin B resistance gene. A second round of transfection and selection in mouse BALB/3T3 fibroblasts again led to isolation of a transfectant susceptible to infection by ALSV-A. Plasmid DNA sequences linked to chicken DNA during the primary transfection segregated with chicken DNA in the secondary transfectant and served as a molecular tag to clone the gene conferring susceptibility. Expression of the cloned gene in mouse BALB/3T3 cells conferred susceptibility to infection by ALSV-A but not by ALSV-B. Therefore the cloned gene most probably represents the tv-a locus, the genetically defined receptor gene for ALSV-A.